The role of organizational membership in overcoming dissonant sport activity identities. Issue 3 (June 2020) - Wegner, Christine E.; King, Ceridwyn; Jordan, Jeremy S.
Highlights: Organizational members use scaffolding to overcome dissonance to running. Organizational members form identities as runners through negotiation strategies. Members become modellers of a running identity for new members. An organization can facilitate running as a normative identity in a community. Organizations may have the capacity to shift dominant social perceptions in sport. Abstract: Forming a strong identity with a sport or activity is a key variable that informs sustained behaviour of that activity. As identities are informed by social forces, marginalized and underrepresented groups face social barriers to embodying a non-traditional sport or activity. Given the power of organizational identities, it may be possible for sport organizations to facilitate salient identities for groups for whom the sport/activity was previously considered dissonant. In this study, the authors used interviews to explore the identity formation processes for members of a national running group for Black women in the United States. Results indicate that members overcame their dissonance to running through their identification with the organization who they felt facilitated education, support, and the connection to existing members who served as identity models. Through their own negotiation strategies, they were able to form a salient identity around the activity, and contribute to a growing collective running identity for this group as a whole.